2010
DOI: 10.1055/s-0030-1250117
|View full text |Cite
|
Sign up to set email alerts
|

Antitussive Effect of Naringin on Experimentally Induced Cough in Guinea Pigs

Abstract: The mechanism of action of naringin has been investigated in different models of experimentally induced cough in guinea pigs. In contrast to codeine phosphate (6 mg/kg, intravenous administration [i. v.]), naringin (15, 30, and 60 mg/kg, i. v.) had no central antitussive effect on cough elicited by electrical stimulation of the superior laryngeal nerve. Naringin (0.5, 1.0, and 2.0 µmol) could not prevent the cough reflex induced by stimulation of the trachea after intracerebroventricular injection (i. c. v.), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Smoke-exposed guinea pigs with enhanced cough are suitable for assessing the antitussive effect of candidates on pathological cough [26]. The peripheral antitussive effect of naringin on non-pathological cough had been confirmed in healthy guinea pig models [14]. Here we further demonstrated the antitussive effect of naringin on enhanced cough and inhibiting effect on AHR in this guinea pig model of smokeinduced chronic bronchitis.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Smoke-exposed guinea pigs with enhanced cough are suitable for assessing the antitussive effect of candidates on pathological cough [26]. The peripheral antitussive effect of naringin on non-pathological cough had been confirmed in healthy guinea pig models [14]. Here we further demonstrated the antitussive effect of naringin on enhanced cough and inhibiting effect on AHR in this guinea pig model of smokeinduced chronic bronchitis.…”
Section: Discussionsupporting
confidence: 64%
“…Naringin can exert expectorant effect via promoting tracheal cilia movement, inhibiting the over expression and secretion of MUC5AC and MUC5B mucin, and preventing the hyperplasia of airway goblet cells [13]. Naringin also exhibits peripheral antitussive effect in experimental cough models in guinea pigs [14]. Besides, it has been reported that naringin could suppress the AHR and eosinophilic airway inflammation in OVA-induced asthma and attenuate acute neutrophilic airway inflammation in LPS-induced acute lung injury in mice through blocking the NF-κB pathway [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment with naringin (18.4 mg/kg) substantially inhibited both enhanced cough and airway neurogenic inflammation in cigarette smoke-exposed guinea pigs [16,18]. Gao et al [22] observed an antitussive effect of naringin at 30 mg/kg in guinea pigs and pointed out that naringin was not a central antitussive drug. Moreover, naringin did not exert its peripheral antitussive effect through either the sensory neuropeptides system or the modulation of ATP-sensitive K(þ) channels.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have shown that naringin has multiple bioactivities, including anti-infl ammatory [ 1 ] , anti-oxidation [ 2 ] , anti-ulcer [ 3 ] , anti-atherogenic [ 4 ] and anticancer [ 5 ] activities. Recently, we demonstrated that naringin, purifi ed from the aqueous extract of Huajuhong with purity over 98 %, was an eff ective peripheral antitussive [ 6 ] by signifi cantly inhibiting the responses of rapidly adapting receptors (RARs) [data to be published], which evoke cough refl ex and are distributed to the organs of trachea and lung [ 7 ] . Thus it could avoid side eff ects such as sedation, nausea, addictive potential, and constipation, often caused by centrally-acting antitussives [ 8 ] .…”
Section: Tissue Distribution Study Of Naringin In Rats By Liquid Chromentioning
confidence: 99%